Exploring associations between household environmental factors and handwashing with essential agents in sub-Saharan Africa. - Aiggan Tamene; Aklilu Habte; Mihretu Tagesse; Fitsum Endale; Tamirat Melis; Zablon Wale Sewalem; Abel Afework (PLoS ONE)
Background 3 billion people lack proper home hand hygiene facilities globally. Of these, 1.4 billion (18%) lack soap or water, while 1.6 billion (22%) have neither. This analysis explores the link between living conditions and the use of essential agents in sub-Saharan Africa. This secondary data analysis examines potential associations between the domiciliary environment and the use of essential agents in sub-Saharan Africa. Methods Eighteen demographic and health surveys were used to analyze the association between household environmental factors and handwashing with essential agents. STATA version 16 was used to analyze data from 203,311 households across weighted samples. Using a multivariable multilevel mixed effect logistic regression analysis, it was possible to determine how each independent factor affected the outcome while taking the data clustering into account. The adjusted odds ratio and its associated 95% confidence interval were used to assess the independent factors' statistical significance. Result Only one in three households 34.84%, practiced handwashing with essential agents, with the highest prevalence in Angola (70.2%) and the lowest in Malawi (6.5%). Educational status [aOR = 1.77; 95%(CI = 1.68-1.86)], female headship[aOR = 1.09; 95%(CI = 1.06-1.2)], household wealth[aOR = 4.08; 95%(CI = 3.84-4.33)], not sharing toilets with other homes[aOR = 1.13; 95%(CI = 1.10-1.17)], having a fixed place for hand washing[aOR = 1.49; 95%(CI = 1.45-1.54)], not having regular access to water [aOR = 0.09; 95%(CI = 0.095-0.10)]and being a rural resident [aOR = 0.85; 95%(CI = 0.82-0.88)] were associated with handwashing. Conclusion sub-Saharan nations are failing to demonstrate advancements in handwashing practices. There are still a lot of homes without access to basic infrastructure for handwashing and household water sources. For essential agent adoption programs to be successful in an environment with limited resources, Water, Sanitation, and Hygiene measures must be implemented. Furthermore, it is critical to include contextual factors from the current study as well as socio-cultural and psychological characteristics that dissuade people from using essential agents in intervention strategies.